(untitled) (Journal of Contemporary Philology, 2025)
The article analyzes interference phenomena in the syntax of clitics in Bulgarian dialects that have been in contact with the Romanian language over a long period of time. The analysis focuses on Bulgarian dialects spoken in the territory of Romania, as well as the specific dialect of Novo Selo in northwestern Bulgaria. It is assumed that both Romanian syntax and dialectal features introduced by Macedonian settlers have influenced this dialect. The principles of clitic order in the sentence, characteristic of Standard Bulgarian, are largely preserved in these dialects. This is mainly due to the fact that both the donor and recipient languages belong to the group of languages with verb-oriented clitics. The analysis shows that in the examined Bulgarian dialects, clitics can appear in initial position, which means that the Tobler-Mussafia law is violated under the influence of the contact languages. At the same time, most of the restrictions on initial clitic placement present in the donor language are shown to be irrelevant.